Participation and decision making in Luganda : an appraisal and genre-theoretic investigation of spoken discourse at community development project meetings - Kabugo, Merit Ronald (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.